Common Mistakes Made in Clinical Research Ethics Committee Applications: Experience of a Training and Research Hospital - LÜLECİ, NİMET EMEL; HIDIROĞLU, SEYHAN (My University, 2022)
Introduction: It is the responsibility of the ethical committees to ensure that the studies carried out on volunteers are carried out in accordance with ethical rules. In this study, it is aimed to analyze the deficiencies in the 2018-2021 application forms of the Istanbul Haydarpaşa Numune Training and Research Hospital Clinical Research Ethics Committee. Methods: The number of applications and revisions, the quality and type of research, area of application and acceptance rate were analyzed retrospectively in the archives of the ethics committee, in 598 files that were finalized between January 2018 and December 2020. Results: In the examined period, the total number of applications has doubled as of the end of 2020 compared to January 2018 (131, 194 and 273 for the years 2018, 2019 and 2020, respectively), and almost all of the applications are non-pharmacologic clinical trials. Among these studies, the highest number of applications are individual research projects, and more than half of them are prospective (63.06%, 66.46% and 58.30%, respectively). The number of applications for which corrections were requested is 77 (58.77%), 107 (55.15%) and 107 (39.19%) according to years. Most of the corrections requested are method related. The highest increase in the number of revisions was in the misidentification of the research type (0.78%, 6.02% and 6.94% for 2018-2020, respectively). Discussion and Conclusion: It was determined that the researchers had difficulties in the study methodology, informed consent and preparation of the scientific basis. Planning periodical Good Clinical Practices (GCP) trainings on an institutional basis under the leadership of ethics committees and that the specialty students have completed their current GCP training before starting their specialty thesis studies will ensure that the research projects to be carried out will be of higher quality in terms of ethics and science
Keywords: Clinical research; clinical research ethics committee; clinical research ethics committee application form